Changing role of security alliances in the post-Cold War era - I. A. Istomin; A. V. Levchenko (Вестник Московского Университета. Серия XXV: Международные отношения и мировая политика)
In the aftermath of the Cold War, both scholars and experts frequently questioned the political relevance of security alliances, given the declining intensity of armed conflicts and the decreasing probability of major interstate wars. However, the post-bipolar international reality marked by the burgeoning of new alliances and coalitions, with old associations being reformed and/or expanded in membership rendered these questions obsolete. In fact, states not only continue to consider military alliance as an important foreign policy tool but actively develop new forms of alliances and coalitions. The article identifies the key trends in the evolution of military and political alliances over the period from the 1990s till the 2010s. Firstly, the authors highlight the waning interest of the leading powers towards formalized allied relations, since they increasingly perceive the latter as an unnecessary burden. At the same time, the researchers note that the leading powers adhered to different approaches to alliance and coalition building in the post-bipolar period. While the United States strengthened the transatlantic core (NATO) in the U.S.-centered network of alliances, relying on more flexible plurilateral formats in other regions of the world, Russia, India, and China did not seek to expand their respective blocs, providing collective security guarantees selectively. That said, all major powers share interest in promoting and developing asymmetric alliances both as tools to deter potential opponents and leverages over junior partners amidst the struggle for spheres of influence. Secondly, the authors conclude that the key feature of the post-Cold War coalition-building is the so-called ritual alliance, when military and political commitments are included in the agenda of regional integration groupings as an addition to substantive issues of cooperation rather than the reverse. Finally, in the 1990s and 2010s, the range of formats of an alliance expanded: from the traditional priorities of territorial defense, the focus has shifted towards expeditionary operations as a part of coalitions, the latter including not only sovereign states but also non-state patronage networks. In conclusion, the authors note that the major powers will continue to promote combined forms of alliances, as the loyalty of partners becomes of increasing strategic importance against the background of growing interstate rivalry.